2018
DOI: 10.1002/jcb.26636
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transcriptional activity by the Myt1 and Myt1l transcription factors

Abstract: Myt1 and Myt1l (Myelin transcription factor 1, and Myt1-like) are members of a small family of closely related zinc finger transcription factors, characterized by two clusters of C2HC zinc fingers. Both are widely expressed during early embryogenesis, but are largely restricted to expression within the brain in the adult. Myt1l, as part of a three transcription factor mix, can reprogram fibroblasts to neurons and plays a role in maintaining neuronal identity. Previous analyses have indicated roles in both tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
(93 reference statements)
2
35
0
1
Order By: Relevance
“…Myt1 and Myt1l (Myelin transcription factor 1 and Myt1-like) are two of the three members of a small family of zinc finger transcription factors that are characterized by two clusters of C2HC zinc fingers [6, 7]. The DNA sequence to which these fingers bind has been defined in vitro [8, 9], and evidence from genome wide analyses supports that this is responsible for at least part of the targeting of these factors to DNA [10, 11]. Characterization of the transcriptional activity of the Myt protein family has suggested that they play roles in repression and activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Myt1 and Myt1l (Myelin transcription factor 1 and Myt1-like) are two of the three members of a small family of zinc finger transcription factors that are characterized by two clusters of C2HC zinc fingers [6, 7]. The DNA sequence to which these fingers bind has been defined in vitro [8, 9], and evidence from genome wide analyses supports that this is responsible for at least part of the targeting of these factors to DNA [10, 11]. Characterization of the transcriptional activity of the Myt protein family has suggested that they play roles in repression and activation.…”
mentioning
confidence: 99%
“…In contrast, Myt1l and a Xenopus homolog of Myt1 have been shown to activate transcription from synthetic reporters based on the known consensus site [6, 8]. However, recent evidence suggests that although there are potential differences in activity, regulation of direct target gene expression via the consensus site primarily results in transcriptional repression [11].…”
mentioning
confidence: 99%
“…The more modest effect on Dnajb1-driven transcription could reflect the absence in our construct of an additional Myt-binding site detected at roughly -6 kbp in fibroblasts and neuronal cells (Mall et al, 2017) (Vasconcelos et al, 2016), because 5'-flanking control regions containing this putative binding site were for unknown reasons unclonable. Note that while we were probing the mechanisms for the transcriptionally repressive effects of Myt TFs on stress-pathway genes that we had detected in pancreatic  cells, these out-of-context assays in HEK293T cells showed activation not repression, which we expected based on the similar "reversals" that occurred when testing the AAGTT motifs in artificial in vitro reporter-transfection assays (Bellefroid et al, 1996;Manukyan et al, 2018;Yee and Yu, 1998).…”
Section: Myt1 Binds To Cis-regulatory Sequences Within Stress-responsmentioning
confidence: 77%
“…While Myt TFs were believed to predominantly repress gene transcription in vivo (Mall et al, 2017;Manukyan et al, 2018;Vasconcelos et al, 2016), ChIP-seq studies identified Myt1 or Myt2 motifs that were associated with activation by in vitro assays (Mall et al, 2017;Vasconcelos et al, 2016), suggesting a strong contextdependent ability for Myt TFs to act as activators or repressors. We found equal numbers of up-and down-regulated genes in 6F; Pdx1 Cre β cells from newborn mice (Table S2).…”
Section: Myt Tfs May Have Both Repressor and Activator Activitiesmentioning
confidence: 99%
“…Myt1l is supposed to limit non-neuronal genes expression, take part in neurogenesis and functional maintenance of mature neurons [37] . The glutamic acid-rich fragment is located close to the activation domain, however it was shown to be dispensable in this process [38] . [40,41] .…”
Section: Protein Similarity Between Sars-cov-2 and Human Lcrsmentioning
confidence: 99%